The Relationship between the Competency of Administrators and the Academic Administration under the Office of Sakaeo Primary Educational Service Area 1 - ทำนุ, นารีรัตน์; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to study the competencies of school administrators and academic administration in schools under the Sa Kaeo Primary Educational Service Area Office 1, and to examine the relationship between the competencies of school administrators and academic administration in schools under the Sa Kaeo Primary Educational Service Area Office 1.The sample consisted of school administrators and teachers in schools under the Sa Kaeo Primary Educational Service Area Office 1 determined by using the Krejcie and Morgan Table (Krejcie & Morgan, 1970, p. 608)  and then using stratified random sampling according to school size. The simple random sampling comprised 115 school administrators and 309 teachers altogether of 424 people. The research instrument used for data collection was a questionnaire. The data were analyzed using descriptive statistics, including frequency, percentage, mean (), and standard deviation (S.D.). To examine the relationships between variables, Pearson’s Product-Moment Correlation Coefficient was employed.           The research findings as follows:• The analysis of the relationship between the competencies of school administrators and academic administration in schools under the Office of the Sa Kaeo Primary Educational Service Area 1 showed that, overall, the level of administration was at the highest level in all aspects (x̄= 4.79, S.D. = 0.297). Considering each aspect individually in descending order of the highest, they were: good service (x̄= 4.81, S.D.= 0.404), achievement motivation (x̄= 4.80, S.D.= 0.356), teamwork (x̄= 4.79, S.D.= 0.380), and self-development (x̄= 4.78, S.D.= 0.348).• The analysis of opinions regarding academic administration in schools under the Sa Kaeo Primary Educational Service Area Office 1 revealed that, overall, opinions on academic administration in schools were at the highest level in all aspects (x̄= 4.74, S.D. = 0.328). Considering each aspect individually in descending order of importance, they were: educational supervision (x̄= 4.77, S.D. = 0.362), learning process development (x̄= 4.77, S.D. = 0.377), development and use of educational technology (x̄= 4.75, S.D. = 0.391), school curriculum development (x̄= 4.72, S.D. = 0.404), assessment, evaluation and credit transfer of learning outcomes (x̄= 4.71, S.D. = 0.386), and research to improve the quality of education in schools ( 4.71, S.D. = 0.402).• The analysis of the relationship between the competence of school administrators and academic administration in schools under the Office of the Sa Kaeo Primary Educational Service Area 1 revealed a high and positive correlation (rxy = .845) with statistical significance at the .01 level.